Agro-morphological characterization and assessment of metabolic profiling and anticancer activities in various tribulus (Tribulus terrestris L.) populations - Yasamin Dabaghkar; Ghasem Eghlima; Hossein Behboudi; Mohammadtaghi Ebrahimi; Mansour Ghorbanpour (BMC Plant Biology)
Abstract Tribulus terrestris L. from the family of Zygophyllaceae, which is rich in saponin compounds, especially diosgenin, has various biological properties, such as anti-inflammation, anti-Alzheimer, anti-obesity, anti-diabetes, anti-leukemia, and anti-cancer activities, due to these compounds. This research aimed to study the diversity of agro-morphological and phytochemical traits and anti-proliferative activity against human prostate cancer cells (PC3) of T. terrestris collected from 24 geographical regions in Iran and to select the superior populations for future domestication and breeding projects. The highest coefficient of variations was related to the fruit dry weight (104.77%), shoot dry weight (104.62%), and leaf dry weight (99.83%). Maximum plant height (113.96 cm), leaf length (49.39 mm), leaf width (23.48 mm), fruit diameter (11.42 mm), and fruit dry weight (34.11 g/plant) were recorded in SBU population. Gallic acid, 3.4dhb, rutin, salicylic acid, quercetin, kaempferol, apigenin, chlorogenic acid, caffeic acid, p-coumarin, ferulic acid, and rosmarinic acid were identified as the main phenolic compounds by HPLC. The highest total saponin content was observed in the RAF population (9.46 µg OCE/g DW) and the lowest in the KER population (4.75 µg OCE/g DW). The minimum (0.65 mg/g DW) and maximum (7.49 mg/g DW) diosgenin content was observed in KHA and PAN populations, respectively. The results of the MTT assay demonstrated the significant anti-proliferative activity of the T. terrestris extracts against the PC3 cancer cell line. IC50 calculated for the T. terrestris extracts in the 24-h treatment was from 15.02 to 27.11 µg/ml, implying that all samples had considerable cytotoxicity activity against the PC3 cells. The diversity observed among the T. terrestris populations in the studied traits shows its high potential for selecting and using the best populations in domestication, breeding, and cultivation projects.